PCAF-mediated acetylation of transcriptional factor HOXB9 suppresses lung adenocarcinoma progression by targeting oncogenic protein JMJD6. Issue 22 (8th September 2016) - Wan, Junhu; Xu, Weizhi; Zhan, Jun; Ma, Ji; Li, Xueying; Xie, Yuping; Wang, Jiadong; Zhu, Wei-guo; Luo, Jianyuan; Zhang, Hongquan
Abstract: HOXB9 is a homeobox domain-containing transcription factor, playing an important role in embryonic development and cancer progression. However, the precise post-translational modifications (PTMs) of HOXB9 and the corresponding roles are unclear. Here, we report that acetyltransferase p300/CBP-associated factor (PCAF) interacts with and acetylates HOXB9 both in vivo and in vitro . Conversely, the acetylation of HOXB9 can be reversed by deacetylase SIRT1. Furthermore, we found that HOXB9 is acetylated at lysine 27 (AcK27). Functionally, in contrast to the wild type HOXB9, AcK27-HOXB9 decreased its capacity in promoting lung cancer cell migration and tumor growth in mice. Mechanistically, AcK27-HOXB9 suppresses the transcription of its target gene Jumonji domain-containing protein 6 (JMJD6) by direct occupying the promoter of JMJD6 gene. For clinical relevance, elevated HOXB9 acetylation at K27 predicts a better prognosis in lung adenocarcinoma patients. Taken together, we identified the first PTM of HOXB9 by demonstrating that HOXB9 can be acetylated and AcK27-HOXB9 counteracts the role of the wild-type HOXB9 in regulating lung adenocarcinoma progression.